Barbara Kryżan-Stanojević: Lice i naličje jezične globalizacije: Zagreb: Srednja Evropa, 2009. 159 str. - Kovač, Mija (Slavia Centralis, 2020)
The paper presents the collection Lice i naličje jezične globalizacije, edited by Barbara Kryżan-Stanojević and created in 2007 at the Faculty of Arts in Zagreb as a result of a project of the Ministry of Science, Education and Sports of the Republic of Croatia entitled Suprotstavljanje globalizaciji jezika i kulture.
Keywords: review; Barbara Kryżan-Stanojević; Lice i naličje jezične globalizacije; national languages; globalization